Thermal Impact on the Culturable Microbial Diversity Along the Processing Chain of Flour From Crickets (Acheta domesticus) - Fröhling, Antje; Bußler, Sara; Durek, Julia; Schlüter, Oliver K. (Frontiers in Microbiology, 2020)
The role of insects for human consumption has lately increased in interest and in order to deliver safe and high-quality raw materials and ingredients for food and feed applications, processing of insects is a major pre-requisite. For edible insects a thermal treatment and appropriate storage conditions are recommended to minimize the microbiological risk and the impact of processing methods on the microbial contamination needs to be considered and determined. Based on standard process conditions for the production of Acheta domesticus flour, different heating treatments were used to reduce the microbial load of A. domesticus. In addition, the drying temperature and drying time were varied to determine whether the required residual moisture of <5% can be achieved more quickly with consistent microbial quality. The influence of the process conditions on the microbial community of A. domesticus along the processing chain was finally investigated under optimized process conditions. The total viable count was reduced from 9.24 log10 CFU/gDM to 1.98 log10 CFU/gDM along the entire processing chain. While Bacillaceae, Enterobacteriaceae, Enterococcaceae, and yeast and molds were no longer detectable in the A. domesticus flour, Staphylococcaceae and mesophilic spore forming bacteria were still found in the flour. The results indicate that the steaming process is essential for effectively increasing microbial safety since this processing step showed the highest inactivation. It is recommended to not only evaluate the total viable count but also to monitor changes in microbial diversity during processing to ensure microbial safety of the final product.